Assessment of Choroidal Vascularity and Choriocapillaris Blood Perfusion in Anisomyopic Adults by SS-OCT/OCTA - Wu, Hao; Zhang, Guoyun; Shen, Meixiao; Xu, Renchang; Wang, Pengqi; Guan, Zhenqi; Xie, Zhu; Jin, Zi; Chen, Sisi; Mao, Xinjie; Qu, Jia; Zhou, Xiangtian (Investigative ophthalmology & visual science, 2021)
To explore the association of choroidal vascularity and choriocapillaris blood perfusion with myopic severity in anisomyopes. Refractive error, axial length (AL), and other biometric parameters were measured in 34 anisomyopic young adults. Macular choroidal thickness (ChT) and choroidal vascularity, including total choroidal area (TCA), luminal area (LA), stromal area (SA), and choroidal vascularity index (CVI), were determined from swept-source optical coherence tomography (SS-OCT) vertical and horizontal B-scans. The percentage of choriocapillaris flow voids (FV%) was obtained from en face SS-OCT-angiography. The spherical equivalent refraction (SER) was -3.35 ± 1.25 diopters in the more myopic eyes and -1.25 ± 1.17 diopters in the less myopic eyes (P < 0.001). The interocular difference in SER was highly correlated with that in AL (P < 0.001). The macular ChT, TCA, LA, and SA were smaller in the more myopic eyes than in the less myopic eyes in both vertical and horizontal scans (all P < 0.001). Importantly, the CVIs in vertical and horizontal scans were smaller and the FV% was greater in the more myopic eyes (P < 0.05). In vertical scans, the interocular difference in CVIs was correlated with that in the SER, AL, and ChT (all P < 0.05). The interocular difference in FV% was correlated with that in SER, AL, and vertical and horizontal ChTs (all P < 0.05). Choroidal vascularity and choriocapillaris blood perfusion were lower in the more myopic eyes of anisomyopic adults. These changes were correlated with the severity of myopia and choroidal thinning, indicating that choroidal blood flow is disturbed in human myopia.